Analisis Willingness To Pay (WTP) Pengunjung Terhadap Upaya Menjaga Kelestarian Lingkungan Objek Wisata Pantai Kurenai Di Desa Botu Barani, Kecamatan Kabila Bone, Kabupaten Bone Bolango - Hippy, Anggriyani; Yusuf, Daud; Mohamad, Nurdin (Universitas Negeri Gorontalo, 2024)
This research aims to find out how much value Willingness To Pay has on environmental sustainability and what factors influence willingness to pay at the Kurenai Beach tourist attraction using a research method, namely a qualitative descriptive method. Data collection in this research used observation, interviews and literature study methods. The population used in this research was tourist visitors and Kurenai beach managers, with a sample size of 50 respondents. The reason the researcher took research on the Willingness To Pay (WTP) analysis of visitors regarding efforts to preserve the Kurenai Beach tourist attraction, is because the sustainability of the tourist attraction is still not good, therefore the researcher took this research on WTP to find out how many visitors or tourists who are willing to pay for the preservation of the Kurenai beach tourist attraction. The results of this research show: (1) research based on the characteristics of respondents, where more respondents were female with an average age of 21-22 years with a type of work, namely as a student and an income of IDR 100,000 - IDR 500,000. (2) the perception of Kurenai beach visitors based on cognitive, affective and conative aspects can be concluded as falling into the agree category and each has an average of 2.29 and 3.37. (3) The average maximum WTP for visitors is IDR 7,500, this is an increase of IDR 2,500 from the initial entrance ticket of IDR 5,000. (4) Factors that significantly influence willingness to pay are gender, age, occupation and income.